Empirical Analysis of Corporate Savings in Egypt - Love, Inessa (2012)
This paper presents empirical analysis of corporate savings in Egypt using two datasets: a survey of small and medium enterprises and data from accounting statements for the largest publicly traded firms. There are two main findings. First, larger firms invest more (they have more physical saving) and have greater access to finance than smaller firms. Second, despite the financial deepening, the use of credit products has been declining during the past decade. The study reaffirms the importance of improving access to financial services in Egypt and points out the need for more research. In addition, policies aimed at reducing macroeconomic volatility are likely to result in increased investment and growth in Egypt.